Occurrence of Brettanomyces bruxellensis on Grape Berries and in Related Winemaking Cellar - Oro, Lucia; Canonico, Laura; Marinelli, Valentina; Ciani, Maurizio; Comitini, Francesca (Frontiers in Microbiology, 2019)
The spoilage yeasts belonging to the genus Dekkera (anamorph Brettanomyces) are associated with the fermentation process and can be responsible for off-flavors in wine. Brettanomyces bruxellensis is difficult to isolate from natural environments because of its low diffusion, low presence on the grape surface and low competition capacity, slow growth and VBNC (viable but not culturable) state, even when selective media are used. In this study, to investigate the origins and occurrence of B. bruxellensis in winemaking, a total of sixty-two samples from grapes, winery environment, and fermenting musts were taken through direct isolation with a selective medium. B. bruxellensis was not directly detected in the grape samples but was instead widely isolated from the winery environment samples. However, using a combination of enrichment and selective media, eight of fifteen grape samples were positive for B. bruxellensis. Analysis of the genetic traits of the isolates indicated a strict relationship among the strains from the vineyard and the winery. Isolates from the vineyard and the winery were both part of the more common and dominant biotypes suggesting that the vineyard may be the contamination source of B. bruxellensis in the winery environment. For this, grapes may represent the possible primary origin source from which a flow towards the winery environment originates. On the other hand, the wide occurrence of B. bruxellensis in winery indicates that this environment can be considered as the favorable ecological niche for colonization and diffusion of these yeast.